Impact Of Low Frequency Trading On Equity Market With Reference To Bse In India - Dr. J. P. Bhosale, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2020)
Economic activities require funds being arranged through various sources such as own funds, borrowings, issue of securities, etc. Among securities, equity shares are issued in the capital markets. Bombay Stock Exchange is one of the capital markets where equity shares are traded. Investors frequently trade in such equityshares of their choice. Hence, numerous trading frequencies take place in a trading day. Such trading frequencies influence on share price changeduring a trading day. Hence, the statement is “Impact of Low Frequency Trading on Equity Market with Reference to BSE in India”. Thus, the lower the trading frequency, the lower are share price changes. The main objective of this study is to examine the impact of low frequency trading on share price change duringJanuary, 2020 to May, 2020. The required secondary data was collected from www.bseindia,com. Analysis and interpretation are done to test a hypothesis that low frequency trading hasnegative impact on share price change. The results revealed that low frequency trading hadnegative impact as well as positive impact on share price change on BSE 30 companies. The study suggests that more variables may be covered for a future study.